STRATEGI PEMBELAJARAN PKN BERBASIS KARAKTER DALAM PENGUATAN PROFIL PANCASILA PADA SISWA MADARSAH IBTIDAIYAH - Iskandar, Rusdy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to explore various effective character-based Civic Education (PKn) learning strategies for implementation with Madrasah Ibtidaiyah (MI) students. The method used was a literature review (library research) involving the collection and analysis of various relevant sources, including scientific journals, books, and reading materials obtained within the framework of the concepts and proceedings listed in the reference list. The results of this study indicate that PKn learning strategies in strengthening the Pancasila profile are highly interrelated. Effective character-based PKn learning strategies in MI include: (1) incorporating the Pancasila lesson profile into Civic education; (2) reinforcement through school cultural habituation; (3) teacher strategies in providing examples, issues, or actual events; (4) role-playing methods for the internalization of values; and (5) the integration of Islamic values with civic values. The implementation of these strategies has proven effective in fostering the development of the six main dimensions of the Pancasila Profile among elementary madrasah students.